2014
DOI: 10.1002/jsfa.6920
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritive quality and protein production from grain legumes in a boreal climate

Abstract: BACKGROUND: Boreal cropping systems are heavily focused on the production of small-grain cereals; to improve their resilience to climate change and to achieve food and feed security, diversification is needed. This study investigated the potential of faba bean, narrow-leafed lupin and lentil as protein crops in southern Finland, where faba bean is traditional but the other two are novel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
78
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 41 publications
(66 reference statements)
15
78
4
2
Order By: Relevance
“…This is despite grain legumes representing a significant source of protein for food (Vaz Patto et al, 2014; Multari et al, 2015) and feed (Jezierny et al, 2010; Koivunen et al, 2014), and legume cultivation reducing the need for N fertilizer even for subsequent crops in the rotation (Preissel et al, 2015). Recent studies have identified a comparative lack of breeding investment in Europe to improve grain legume adaptation to local agro-climatic conditions and management techniques (Annicchiarico and Iannucci, 2008; Lizarazo et al, 2015). While distinct leguminous crops are used locally for food and feed, and local cultivars are kept in numerous collections in gene banks, research institutions, and also in farms/home gardens, this genetic pool cannot be used at its full potential for large-scale agriculture and breeding programs until important traits have been determined.…”
Section: Introductionmentioning
confidence: 99%
“…This is despite grain legumes representing a significant source of protein for food (Vaz Patto et al, 2014; Multari et al, 2015) and feed (Jezierny et al, 2010; Koivunen et al, 2014), and legume cultivation reducing the need for N fertilizer even for subsequent crops in the rotation (Preissel et al, 2015). Recent studies have identified a comparative lack of breeding investment in Europe to improve grain legume adaptation to local agro-climatic conditions and management techniques (Annicchiarico and Iannucci, 2008; Lizarazo et al, 2015). While distinct leguminous crops are used locally for food and feed, and local cultivars are kept in numerous collections in gene banks, research institutions, and also in farms/home gardens, this genetic pool cannot be used at its full potential for large-scale agriculture and breeding programs until important traits have been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The yields from the field trials developed in the present work were rather low in comparison with the average yield in the region, which ranges from 0.30 to 0.49 kg m −2 . Such low yield is not a result of the cropping variants assayed, but due to the unfavourable and critical weather conditions – low precipitation events during the seed growth period – at the beginning of August for both seasons.…”
Section: Resultsmentioning
confidence: 57%
“…Regarding protein content in the faba bean seeds, in 2014 and 2015, a significant influence of the faba bean genotype and growing conditions (influenced by the particular climatic features of each season) was found, whilst the intercrop variant remained a less relevant factor with no significant influence …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations